Early patent disclosure and R&D investment in family firms - Katrin Hussinger; Wunnam Issah (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper shows that the American Inventor's Protection Act, which introduced the disclosure of patent applications after 18 months, i.e. before a grant decision is taken and, hence, before it is known whether the respective technology receives legal protection, is associated with a reduction of family firms' research and development (R&D) investment. This suggests that early disclosure of patent applications is perceived as a threat to family firms' innovation activity and discourages their R&D investment. This finding deserves our attention because family firms account for a large share of the U.S. economy and a reduction of their R&D investment can have long-term consequences.
Keywords: O32; M14; O34; 330; R&D investments; AIPA; Family firms; Socio-emotional wealth (SEW)